1992
DOI: 10.3758/bf03211653
|View full text |Cite
|
Sign up to set email alerts
|

Active regulation of altitude as a function of optical texture

Abstract: Two empirical studies are reported that examine active regulation of altitude as a function of the type of ground texture. Three ground textures were examined: lines perpendicular to the direction of motion, lines parallel to the direction of motion, and the combination (i.e., square or checkerboard texture). Although subjects only controlled altitude, disturbances were introduced on three axes: vertical, lateral, and fore-aft. The results show a clear advantage for texture parallel to the direction of motion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…In a comprehensive study, Mulder (1999Mulder ( , 2003 showed that surfaces play a crucial role in understanding the way pilots perceive the aircraft locomotion state from the three-dimensional tunnel geometry motion perspective. Motion relative to a surface yields an optical expansion pattern that contains very useful information about the observer's motion (Flach, Hagen, & Larish, 1992;Gibson, 1950Gibson, , 1979Gibson, /1986): the texture gradients. Visualizing energy through a surface, the TERP, aims at enabling pilots to directly perceive the aircraft energy state through the texture gradients resulting from the aircraft motion relative to the energy surface (Amelink, 2002).…”
Section: Perceiving the Energy Cues From The Energy-augmented Tunnel mentioning
confidence: 99%
“…In a comprehensive study, Mulder (1999Mulder ( , 2003 showed that surfaces play a crucial role in understanding the way pilots perceive the aircraft locomotion state from the three-dimensional tunnel geometry motion perspective. Motion relative to a surface yields an optical expansion pattern that contains very useful information about the observer's motion (Flach, Hagen, & Larish, 1992;Gibson, 1950Gibson, , 1979Gibson, /1986): the texture gradients. Visualizing energy through a surface, the TERP, aims at enabling pilots to directly perceive the aircraft energy state through the texture gradients resulting from the aircraft motion relative to the energy surface (Amelink, 2002).…”
Section: Perceiving the Energy Cues From The Energy-augmented Tunnel mentioning
confidence: 99%
“…The projection of lines perpendicular to the viewing direction conveys optical-density information, representing the gradient of compression. In the 1980s a large number of studies investigating the task of the visual perception and control of self-motion confirmed Gibson's hypotheses, (e.g., Warren & Owen, 1982;Warren, 1988; see Owen, 1990 or Flach, Hagen, andLarish, 1992 for excellent overviews).…”
Section: Exploring the Information For Locomotion Available In Naturamentioning
confidence: 89%
“…. with respect to the amount of activity in that optical variable that is not specific to the variable to be controlled" (Flach et al, 1992). Now, motion states belonging to the same control channel can be coupled, motion states belonging to different control channels can be coupled, or there can be a mixture of these situations.…”
Section: Assessing the Relative Usefulness Of The Visual Informationmentioning
confidence: 99%
“…Apart from general cues such as optical edge-and flow rate and texture [6][7][8], the 'implicit horizon' (distance between the horizon and the aim point, measured in the visual plane; Y-H in Fig.1) is often mentioned as an important cue [9][10][11][12], especially for keeping the preferred glide slope. The position of the horizon (Y) is known to have a close relation to the pitch of the aircraft.…”
Section: Visual Perception During Landingmentioning
confidence: 99%